“‘Yeyedi’ ‘Velinga’ ‘Agbe nyue nᴐnᴐ’ ‘Shihilԑ kpakpa’: In Search of Local Concepts of Well-Being in Akan, Dagbani, Ewe, and Ga” - Osei-Tutu, A. (My University, 2019)
Well-being is an important concept to psychologists, public health practitioners, religious leaders, national leaders, and policymakers. The third goal of the United Nations’ Sustainable Development Goals (SDGs) aims at promoting well-being and healthy lives. Normative conceptions of well-being are often influenced by values and ideals associated with North American and some European worlds. Such conceptions of well-being tend to valorize self-acceptance, personal growth, and autonomy, which do not resonate with Ghanaian ways of being. Research and conversations on well-being in most West African settings often adopt languages and concepts that the ordinary people cannot readily relate to. Alternative understandings of well-being that exist within most West African settings remain unknown and make attempts of promotion difficult. It is important to capture local conceptions of well-being and incorporate them into existing health promotion interventions, as well as create new avenues for promotion. Given the importance of well-being to the Psy-disciplines and the global mental health agenda to promote health and well-being, this study adopted a social constructivist approach to investigate constructions of well-being among local cultural experts in Ghana. Participants identified and explained constructs that are related to the concept of well-being in four Ghanaian languages (Akan, Dagbani, Ewe, and Ga). In this presentation, I aim to stimulate discussions, which will further our understandings of well-being, that will resonate with the Ghanaian people.
Seminar
Keywords: Akan; Dagbani; Ewe; Ga; Ghana